Optical properties of chalcogenide (As2S1.5Se1.5)0.99:Sn0.01 thin films - Iaseniuc, Oxana (D.Ghitu Institute of Electronic Engineering and Nanotechnologies, 2010)
In this work, we carried out measurements of optical constants (refractive index n, ab-